Effect of psychoeducation in reducing caregiver burden among family caregivers of people with mental disorders in Western Ethiopia, 2021–2022: A pre-test post-test study - Adamu Kenea; Sudhakar N. Morankar (PLoS ONE, 2026)
Background Family caregivers of individuals with mental disorders experience significant financial, emotional, and psychological burden, particularly in low-resource settings with limited access to formal mental health services. Although psychoeducation is an effective strategy for reducing caregiver burden, evidence from low- and middle-income countries, including Ethiopia, remains scarce. Objective To assess the effectiveness of a structured psychoeducation intervention in reducing caregiver burden among family caregivers of individuals with mental disorders attending Nekemte Comprehensive Specialized Hospital, Nekemte Town, and Mettu Karl Comprehensive Specialized Hospital, Mettu Town, Southwest Ethiopia. Methods A pretest–posttest quasi-experimental study with an intervention and a comparison group was conducted from March 2021 to February 2022 at Mettu Karl Comprehensive Specialized Hospital and Nekemte Comprehensive Specialized Hospital in Oromia, Ethiopia. The sample size was determined using G*Power software, yielding a total of 556 family caregivers (intervention: n = 279; comparison: n = 277). Family caregivers were systematically sampled, with Mettu Karl Comprehensive Specialized Hospital assigned to the intervention group and Nekemte Comprehensive Specialized Hospital to the comparison group, which received routine care. The intervention consisted of six monthly structured group psychoeducation sessions. Caregiver burden was measured at baseline and post-intervention using the Zarit Burden Interview. The data were entered into SPSS version 25 for analysis. Intervention effects were assessed using linear mixed-effects models and difference-in-differences analysis. Ethical approval was obtained from the Institutional Review Board of Jimma University. Results There was a significant difference in mean caregiver burden scores between the intervention and comparison groups (p < 0.001). The intervention group demonstrated a significantly greater reduction in burden compared to the comparison group (DID =−4.32; 95% CI: −6.83, −1.81). After adjusting for socio-demographic and clinical factors, the linear mixed-effects model showed a significant reduction in caregiver burden among the intervention group (β =−5.65; 95% CI: −7.35, −3.95; p < 0.001). Conclusion The structured psychoeducation intervention was effective in reducing caregiver burden among families of individuals with mental disorders in Southwest Ethiopia. These findings support the integration of culturally appropriate psychoeducation programs into routine and community-based mental health services, particularly in resource-limited settings where family caregivers play a central role in patient care.